Unpacking strategic behavior in cyberspace: a schema-driven approach. Issue 1 (26th April 2022) - Gomez, Miguel Alberto; Whyte, Christopher
Abstract: The contemporary literature on cybersecurity and related interstate interactions often cites the need to overcome uncertainty due to an inherent information deficit about cyber operations. While this notion remains relevant in studies that advance our understanding of state behavior in cyberspace, noticeable gaps persist. These stem from the limited utility of cyber operations to shift the balance of strategic power between states or to signal intent and resolve effectively. In response, this article advances a cognitive-cultural framework, wherein behavior reflects preferences derived from schema usage. Using cross-national wargames, the article illustrates the schematic use of strategic culture as a basis for deriving strategic objectives and the means of achieving these. Consequently, the article is an initial foray aimed at expanding our understanding of interstate behavior in cyberspace.